2021
DOI: 10.1002/ccr3.5049
|View full text |Cite
|
Sign up to set email alerts
|

Isolated tuberculosis liver abscess in an immunocompetent patient

Abstract: Isolated TLA is an extremely rare condition, but should always be considered in a patient presented with liver abscess, especially from an endemic area. Diagnosis depends on histological identification, with treatment being quadruple therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(14 reference statements)
1
0
0
Order By: Relevance
“…To avoid local and systemic significant consequences, it is necessary to detect and evaluate for MTB as a causative agent for liver abscess. Similar cases have been reported before by several authors, including Yazan et al in 2021 [ 7 ] and Devi et al in 2019 [ 8 ], who likewise concluded that isolated tubercular liver abscess is a rare condition. However, it should be considered as differential diagnosis in endemic areas.…”
Section: Discussionsupporting
confidence: 87%
“…To avoid local and systemic significant consequences, it is necessary to detect and evaluate for MTB as a causative agent for liver abscess. Similar cases have been reported before by several authors, including Yazan et al in 2021 [ 7 ] and Devi et al in 2019 [ 8 ], who likewise concluded that isolated tubercular liver abscess is a rare condition. However, it should be considered as differential diagnosis in endemic areas.…”
Section: Discussionsupporting
confidence: 87%